Green’s relations on the seminearring of full hypersubstitutions of type (n) - Changphas, Th.; Denecke, K. (Algebra and Discrete Mathematics, 2003)
Hypersubstitutions are mappings which are used to define hyperidentities and solid varieties. In this paper we will show that the set of all hypersubstitutions of a given type forms a seminearring. We will give a full characterization of Green’s relation R on a sub-seminearring of the seminearring Hyp(n) of all hypersubstitutions of type (n).